2013
DOI: 10.1007/s00221-013-3576-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mechanical load on sequential effects

Abstract: Almost two decades ago, sequential effects of human grasping behaviour were described for the first time: In a sequential task, participants persisted in using the previous grasp type. According to the plan-modification hypothesis, such sequential effects reduce the movement planning costs and occur within a limited range of indifference. In the current study, we asked whether the anticipated mechanical costs of a movement would compete with the movement planning costs and, thus, reduce the magnitude of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 32 publications
5
27
0
Order By: Relevance
“…These models determined hand choice based on the lowest biomechanical costs but differed in their assumptions about future body acceleration when the cost computations were performed. These models, accounting for hand choice based on biomechanical cost functions, cannot be taken to suggest that no other cost functions play a role in this form of decision making, such as, for example, cognitive costs (Schütz and Schack 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These models determined hand choice based on the lowest biomechanical costs but differed in their assumptions about future body acceleration when the cost computations were performed. These models, accounting for hand choice based on biomechanical cost functions, cannot be taken to suggest that no other cost functions play a role in this form of decision making, such as, for example, cognitive costs (Schütz and Schack 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This cognitive cost becomes visible when participants carry out repetitive tasks. When opening a series of drawers with cylindrical handles, participants persist in their previous posture, i.e., a more pronated posture in a descending and a more supinated posture in an ascending sequence (Schütz and Schack 2013;Schütz et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The study of Cohen and Rosenbaum (2004) also demonstrated that action planning is not only influenced by upcoming task demands, but also by previously performed actions (see also Rosenbaum and Jorgensen, 1992 ; Jax and Rosenbaum, 2007 ; van der Wel et al, 2007 ; Weigelt et al, 2009 ; Schütz et al, 2011 ; Schütz and Schack, 2013 ). Specifically, after participants had placed the plunger at the target platform, they lowered their arm, and then transported the plunger back to the home platform (target-back-to-home moves).…”
Section: Introductionmentioning
confidence: 90%